2019
DOI: 10.1002/cam4.2250
|View full text |Cite
|
Sign up to set email alerts
|

Comparison  of  efficacy, safety, and costs between neoadjuvant hypofractionated radiotherapy and conventionally fractionated radiotherapy for esophageal carcinoma

Abstract: Background We compared the efficacy, safety, and costs of hypofractionated radiotherapy (HFRT) and conventional fractionated radiotherapy (CFRT) for the neoadjuvant treatment of esophageal cancer. Materials and Methods Overall, 110 patients with esophageal cancer treated with neoadjuvant chemoradiotherapy from October 2002 to July 2017 were retrospectively included and divided into a HFRT group (42 patients received 30 Gray [Gy]/10 fractions for 2 weeks) and a CFRT grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…With advances in the planning and delivery of conformal radiation, there has also been growing interest in hypofractionation (>2 Gy per daily fraction with lower cumulative dose). 31 This approach may be beneficial for elderly patients given reduced treatment duration with potentially improved tolerability.…”
Section: Discussionmentioning
confidence: 99%
“…With advances in the planning and delivery of conformal radiation, there has also been growing interest in hypofractionation (>2 Gy per daily fraction with lower cumulative dose). 31 This approach may be beneficial for elderly patients given reduced treatment duration with potentially improved tolerability.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the use of hypofractionation in the curative setting for oesophageal cancer, there is an increasing volume of evidence demonstrating the safety and efficacy of this approach[ 27 ]. There are studies demonstrating a survival benefit of this approach particularly in the context of metastatic nodal disease.…”
Section: Discussionmentioning
confidence: 99%
“…54 Another study from China reported that neoadjuvant 10-fraction hypofractionated radiation for esophageal cancer resulted in a 41% reduction in radiotherapy costs over a 20-fraction moderately hypofractionated regimen. 53 Reducing the treatment costs patients incur is equally important to reducing the costs for the overall health care system. The cost associated with traveling, finding housing, and missing work can carry staggering consequences for patients.…”
Section: Reduced Costsmentioning
confidence: 99%